Agriculture Innovation Strategy to Support Food Security in Padang Pariaman District, West Sumatera Province - Herman Yaarozatulo Harefa (International Journal of Regional Innovation, 2021)
Public service can be defined as providing services (serving) the needs of people or communities who have an interest in accordance with predetermined basic rules and procedures. Public services view the public as a service target so that they are expected to be able to provide the best dedication in serving a more selective and educative public, as well as managing public policies run by the public bureaucracy. In order to create this, an application of innovation is needed. Innovation is an application or an effort to bring new ideas into implementation with a fairly large change of steps, lasts quite a long time and is quite general in scale. Padang Pariaman Regency is one of the rice producers in West Sumatra Province. Not only that, Padang Pariaman also has agricultural potential such as food crops, plantations, and so on. The agricultural sector is a sector that is able to survive and is utilized by the government to overcome the global economic crisis. For this reason, in addition to making innovations related to health and administration, the West Sumatra Provincial Government is focusing on increasing public service innovation in agriculture. This study aims to identify innovations in the West Sumatra Provincial Government related to improving public services within the Government. This research uses descriptive quantitative method. As a result, the Padang Pariaman Regency Government can improve food security, improve agricultural market information services, farm business administration, and increase plantation yields, which can facilitate and improve the lives of farmers. Suggestions for increasing public service innovation in the agricultural sector of Padang Pariaman Regency are expected that the Government can continue to evaluate the innovations that have been implemented.